A Four-Tier Diagnostic Instrument in Acid-Base Properties of Salt Solution: Development Procedure - Rima Nuraini (PT Ahan Group Publisher, 2025)
This study aims to determine the feasibility of a four-tier diagnostic instrument on salt hydrolysis. The development uses a four-tier diagnostic instrument development procedure by Habiddin & Page (2019) with 6 stages: concept identification, initial test and interview, identification of unscientific student concepts, development of a four-tier diagnostic instrument prototype, prototype validation, and final prototype improvement. The four-tier diagnostic instrument was developed from a multiple-choice instrument open to reasons for capturing student concepts. At last, the finding from this research and development obtained the final product in the form of a four-tier diagnostic instrument with 27 questions that have four levels (tier), the first tier is in the form of questions and answers, second tier is in the level of confidence in the answer chosen, third tier is in the form of selecting the first tier, and the fourth tier is the level of confidence in the reasons chosen. The level of confidence is measured on a scale of 1-5. The instrument developed has an average content validity of 89.45%, with a very decent category and very high reliability (0.858). This shows that the developed four-tier diagnostic instrument is highly feasible for identifying students' misconceptions about salt hydrolysis material.